Childhood disability in Sumy region: territorial and demographic aspects - Moskalenko, Mykola; Kornus, Olesia; Kornus, Anatolii (Human Geography Journal, 2025)
The article presents data on childhood disability (under 18 years) for the period 2012-2019 in the Sumy region. An analysis of the dynamics of changes in childhood disability during this period in the Sumy region, the city of Sumy, and the districts of the region was conducted. The study used materials from the State Statistics Service of Ukraine, the Ministry of Health of Ukraine, the Ukrainian Institute for Strategic Studies, the Regional Information and Analytical Center for Medical Statistics in Sumy, and the Main Department of Statistics in the Sumy region. The findings revealed an increase in the level of childhood disability in the Sumy region throughout the entire study period, with a particularly high growth rate observed in the last four years. It was noted that each year of the study, the childhood disability rate in the city of Sumy exceeded the regional average by 4-8%. Congenital developmental anomalies, mental and behavioral disorders, and central nervous system diseases were identified as the leading causes of childhood disability. The study also established that the disability rate among boys in the Sumy region exceeded that of girls by 29-30% annually throughout the study period. Children aged 7-14 years constituted the largest share of the total disabled child population in the region, accounting for 50–54%, with an annual increase observed during the study.